2020
DOI: 10.1177/2374373520918723
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Association Between Chaplain Care and Patient Experience

Abstract: A developing body of evidence indicates that chaplain care is associated with higher levels of patient/family satisfaction with their hospital care. We examined the association between chaplain care and patient experience among patients at Rush University Medical Center in Chicago who responded to Hospital Consumer Assessment of Healthcare Providers and Systems and Press Ganey survey items between 2011 and 2017. Information about chaplain care was taken from the inpatients’ electronic medical record. Our analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
1
5
0
1
Order By: Relevance
“…The ability of chaplains to just sit and listen to patients who could no longer have family members visit was highly valued by both the patients themselves and staff who did not have the time to do so. These findings replicate other studies which have explored the role of chaplaincy in usual times (Best et al, 2020;Damen et al, 2020;Handzo et al, 2008;Taylor et al, 2015). This suggests that, while the COVID-19 pandemic has created a crisis on a world-wide scale, the tools for dealing with this situation lie within the chaplain's standard expertise.…”
Section: Discussionsupporting
confidence: 86%
“…The ability of chaplains to just sit and listen to patients who could no longer have family members visit was highly valued by both the patients themselves and staff who did not have the time to do so. These findings replicate other studies which have explored the role of chaplaincy in usual times (Best et al, 2020;Damen et al, 2020;Handzo et al, 2008;Taylor et al, 2015). This suggests that, while the COVID-19 pandemic has created a crisis on a world-wide scale, the tools for dealing with this situation lie within the chaplain's standard expertise.…”
Section: Discussionsupporting
confidence: 86%
“…In one study of U.S. adults, education level either minimized or amplified an individual's religious involvement based on one's denominational affiliation (McFarland et al, 2011) as well as gender (Norton & Tomal, 2009). Another study reported an inconsistent association between receipt of chaplaincy care and education (Damen et al, 2020). Thus, we hypothesized the following: H2 Education will have no association with receipt or the duration of chaplaincy care.…”
Section: Enabling Factorsmentioning
confidence: 96%
“…There is strong evidence of higher levels of religious involvement among African Americans compared to Whites (Ellison et al, 2010). The use of a chaplain for non-Hispanic populations and those who do not speak English as their primary language may depend on hospital translational services since research has identified mixed findings (Damen et al, 2020;Hyer et al, 2020). In addition, religious patients are Fig.…”
Section: Predisposing Factorsmentioning
confidence: 99%
“…These data have several implications for future education, practice and research. While prior efforts to demonstrate the beneficial aspects of chaplaincy (e.g., attempting to show increased patient ratings in hospital satisfaction scores) have been mixed ( Damen et al., 2020a , Damen et al., 2020b ; Marin et al., 2015 ), the present data suggest other sets of key benefits that chaplains can provide. Given the critical needs to document the benefits of chaplaincy ( Gomez et al., 2021 ; Wirpsa et al., 2019 ), the present data are thus valuable.…”
Section: Discussionmentioning
confidence: 53%
“…Specifically, in one study, 5.6% of patients at one institution saw a chaplain, and were more likely to have higher patient satisfaction on 6 items, regarding religious/spiritual and general psychosocial care activities ( Marin et al., 2015 ). Yet in another, much larger study of 11,741 patients, 26.5% saw chaplains, but were more likely to have poorer health and patient experiences ( Damen et al., 2020a ). The relationships among these variables may thus be complex, since sicker patients may be more likely both to see a chaplain and to have worse prognoses and thus less satisfaction with care.…”
Section: Introductionmentioning
confidence: 99%